O CONTROLE DE CONVENCIONALIDADE FEITO PELO STF DIANTE DECISÕES DA CORTE INTERAMERICANA DE DIREITOS HUMANOS - Arcaro Conci, Luiz Guilherme; Fioramonte Tonet, Livia (Revista Digital Constituição e Garantia de Direitos, 2024)
This document is a presentation of the empirical research in the area of international human rights law carried out for the purposes of the Course Conclusion Work for the São Bernardo do Campo Law School and concerns how the Federal Supreme Court (STF) carries out conventionality control in the face of the decisions of the Inter-American Court of Human Rights (IACHR) in its own decisions. The conclusion is that there is no technique, analysis or method for applying international decisions in the rulings; they are used like other citations and references throughout the text made by the justices. The research path goes through: (i) international human rights law and multilevel constitutionalism; (ii) the dialogue between courts; (iii) constitutionality control; (iv) the Inter-American Court of Human Rights; (v) the Federal Supreme Court; (vi) the individual analyses and the joint analysis of the judgments extracted from the empirical part; and (vii) the conclusion